Employee Engagement Strategy in the Human Capital Directorate (Study Case : Bank X) - Savitri, Christina Amanda; Andika Wahyu Pratama; Izhatullaili (Universitas Tidar, 2024)
Companies need to manage Human Resources (HR) well, so that companies can create good and competent employees. One way is to develop the right employee engagement strategy. This study aims to determine the employee engagement strategy in the human capital directorate of Bank X that is successful in increasing employee engagement. The method used in this research is descriptive qualitative. Data collection techniques using interviews, documentation, and triangulation methods. Data analysis used in this research is data reduction, data presentation, and conclusion dra wing. The sources in this study involved five sources consisting of four employees with manager and staff positions along with one employee with a head division position. The results showed that the implementation of employee engagement strategies in the human capital directorate is divided into five dimensions, namely organization, leadership, team members, work and individuals. However, there are obstacles in implementing employee engagement strategies in the human capital directorate of Bank X, namely due to ineffective communication and employee mindset.